Narrative microstructure and macrostructure in adolescents with Down syndrome and Williams syndrome - Viejo, Aitana; Fernández-Urquiza, Maite; Diez-Itza, Eliseo (Frontiers in Psychology, 2025)
Down syndrome (DS) and Williams syndrome (WS) are genetic neurodevelopmental disorders associated with intellectual disability, showing contrasting linguistic profiles with asymmetries in grammatical (DS weakness/WS strength) vs. pragmatic abilities (DS strength/WS weakness). The aim of the present study was to explore the linguistic profiles of 14 adolescents with DS and WS, and 14 typically developing controls (matched by chronological and verbal age) by comparing the microstructure and macrostructure of narratives and their possible dissociation. Participants watched an episode of the Tom and Jerry cartoon series and were asked to retell it. The videotaped narratives were transcribed and analyzed with the tools of the CHILDES Project and the Pragmatic Evaluation Protocol for Corpora (PREP-CORP). Microstructure was assessed by productivity at the grammatical level (number of utterances) and lexical level (number of word tokens), and complexity at the grammatical level (MLU) and lexical level (number of word types). Macrostructure was assessed by the number of story elements recalled at three levels: scenarios (global), episodes (integrated), and events (detailed). Results confirmed asymmetries in the linguistic profiles of both groups, with relative strengths of adolescents with DS in macrostructure despite relative weaknesses in microstructure. Conversely, adolescents with WS exhibited strengths in narrative microstructure, but failed to show better performance than the DS group in macrostructure. Following regression analyses, microstructure predicted macrostructure in typically developing adolescents, while no association was found between both levels in the profiles of adolescents with WS and DS, which was interpreted as an atypical dissociation.